2017
DOI: 10.1259/bjr.20170007
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion and dynamic contrast-enhanced MRI for differentiation between hepatocellular adenoma and focal nodular hyperplasia

Abstract: In this exploratory study, K and D were able to differentiate HCAs from FNHs in most cases, whereas V, ADC and TIC analysis were not. Advances in knowledge: Histological differences between HCAs and FNHs can be quantified on MRI using K and D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The cellularity of ICC is relatively small and the existed tumor cell could arrange into acinar like structures, thus, which could further prompt the water molecular diffusion and increase the ADC and ADC slow value. Previous studies compared the ADC value of ICC and normal hepatic parenchyma and showed that the value of ICC was lower than the normal hepatic tissue [ 29 ], and some other studies also reported that the ADC value of the HCC was also lower than that of the relatively low cellularity benign nodules [ 30 , 31 ]. These current results were consistent with the findings that low cellularity tumor demonstrated a high ADC value compared with the high cellularity tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The cellularity of ICC is relatively small and the existed tumor cell could arrange into acinar like structures, thus, which could further prompt the water molecular diffusion and increase the ADC and ADC slow value. Previous studies compared the ADC value of ICC and normal hepatic parenchyma and showed that the value of ICC was lower than the normal hepatic tissue [ 29 ], and some other studies also reported that the ADC value of the HCC was also lower than that of the relatively low cellularity benign nodules [ 30 , 31 ]. These current results were consistent with the findings that low cellularity tumor demonstrated a high ADC value compared with the high cellularity tumor.…”
Section: Discussionmentioning
confidence: 99%